Use of Extracorporeal Techniques in the Removal of Dabigatran. (March 2016) - Muddana, Neeharika; Thuyanh, Culver; Nayer, Ali; Nashar, Khaled; Ortega, Luis M.
Abstract : Dabigatran is a novel direct thrombin inhibitor that has proven effective in the prevention of vascular events in patients with nonvalvular atrial fibrillation. Not much is known about the clearance capability with extracorporeal techniques of dabigatran. This review showcases the pharmacokinetics and a perusal of the current literature regarding cases that involved the clearance of the drug in patients with normal renal function and end-stage renal disease. Renal replacement therapy represents a therapeutic option to eliminate dabigatran and decreased the risk of bleeding in patients undergoing emergent surgical procedures on dabigatran.